Biomass As An Alternative Fuel – Selected Aspects - Zeńczak Wojciech; Łuszczynski Daniel (Polish Maritime Research)
In July 2023, the International Maritime Organization (IMO) revised its strategy for reducing greenhouse gas (GHG) emissions from ships. The changes adopted mean that ships should not emit GHGs as early as 2050, not, as originally assumed in the first version of this strategy, 2100. In turn, on 1 January 2025, a European Union regulation (FuelEU Maritime) on ships entering European Union ports with the aim of supporting the decarbonisation of shipping came into force. In this situation, alternative fuels and all technologies related to the use of renewable energy sources on ships, low-emission fuels and clean technologies are of particular importance because they contribute to the reduction of the consumption of fossil fuels. One of the alternative fuels that meets these criteria is ordinary or torrefied timber pellets. This type of fuel requires the use of special transport installation solutions, such as pneumatic solutions. The article presents selected results of experimental tests conducted using a test stand. On their basis, the hypothesis that the pressure drop in the installation depends on various operating states of the ship and the parameters of the transported material was confirmed.